Logistics in a Green Era, a Blockchain-based Framework - Ambrozie, Alisa-Mihaela; Sorcaru, Sergiu (Acta Universitatis Danubius. Œconomica, 2023)
With the promotion of sustainable models, increased attention is being given to ecological logistics and the application of GSCM in an increasing number of industries. Ecological logistics as a concept is viewed as a sustainable model in specialized studies, however, a consistent obstacle is observed in terms of real-time data collection and sharing. This article aims to highlight how the implementation of blockchain technology in logistics can provide a solution to this challenge, through the well-known specific characteristics of blockchain technology, which have already been successfully applied in various fields of activity.